Research on the Making Suitability for Steamed Bread with Wheat Flours from Southwest of Henan Province - WEI Yi-min; ZHANG Lei; ZHAO Bo; YAN Jun-hui; WANG Jiang-hua (Liang you shipin ke-ji, 2023)
Steamed bread is one of the traditional Chinese staple foods. With the increasing in the proportion of mechanized production and market-oriented sales of steamed bread, the steamed bread industry has been developing rapidly. Under the production conditions of industrial steamed bread, the characteristics of wheat varieties and their corresponding flour suitability for making steamed bread, especially the stability of flour, could significantly affect the product quality, consumption experience and economic benefits of industrialized steamed bread. In this study, the physical and chemical properties of flours from wheat varieties with larger planting area and stronger representatives in southwest Henan were analyzed for the suitability of steamed bread, and the relationships between flour and steamed bread quality properties were also studied. The results showed that the wet gluten content of wheat flour in southwest Henan was high, but the gluten index needed to be improved. The proportion of strong-gluten wheat variety also needed to be improved. The values of flour color a* b *, gluten index, the dough softening by Farinograph, the area by Extensograph and the extensibility (L) by Alveograph are important reference indicators for evaluating the quality of flour for steamed bread. The wheat varieties of Zhengmai 119, Pingmai 998, Shaanxi Road 198, Zhengmai 1342, and Zhengmai 1860 are more suitable for making steamed breads.